ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEIKUTSERTAAN SENAM HAMIL PADA IBU HAMIL DI BPS NINA SURABAYA - Laili, Uliyatul (Jurnal Ilmiah Kesehatan, 2015)
Analysis of factors Affecting The Participant Pregnant Women Gymnactics in BPS Nina Surabaya. Pregnant women should get treatment during pregnancy. Treatment during pregnancy or antenatal care can be done via examination of pregnancy, pregnancy exercise, nutrition and other compliance requirements. Pregnancy exercise is an exercise undertaken to prepare and train the muscles so that it can be used to function optimally in a normal delivery.This study uses an analytical method with cross sectional design prospective. Sampling using total sampling technique. The independent variable is education, parity and maternal knowledge, while the dependent variable is exclusive breastfeeding. Data were analyzed using chi square test.The results showed a correlation between age and support of husband / family with the participation of pregnant women during pregnancy exercise with a p-value of <0.05, whereas for education and parity are not related to the participation of pregnant women against pregnancy exercise with a value of p>0.05.The conclusions of this study are the factors that influence the participation of pregnant women during pregnancy exercise is aged and the support of husband / family.